QSA: Query Splitting-Based Anticollision for Mobile RFID-Based Internet-of-Things - Jianliang Gao; Jianxin Wang; Jianbiao He; Weiping Wang (International Journal of Distributed Sensor Networks)
Mobility is a common character of the emerging RFID-based internet-of-things. However, most of prior RFID anticollision algorithms ignore the movement of tags, which can degrade the identification performance seriously and even result in tag starvation problem. This paper presents a novel anticollision algorithm named Query Splitting-based Anticollision (QSA) for mobile RFID-based internet-of-things. By designing adaptive query, QSA reduces the number of collisions efficiently and makes it possible to identify multiple mobile tags without rollback. In QSA, we propose a query stack technology to avoid the rollback operation caused by new arriving tags, which solves the tag starvation problem under mobile environments. The performance evaluation shows that the proposed algorithm takes fewer timeslots and has better performance in identifying mobile tags.